International leadership models in the assumptions of the theory of realism - Brzezińska, Monika (Politologia, 2023)
This article is of theoretical nature and aims to try to define various models of international leadership and their nature in the light of the assumptions of realism. The main research determinants include the ones typical for the abovementioned theory, such as an actor’s identity, its position in the system, as well as the source of power and interdependencies to which it is subjected. These, on the other hand, may turn out to be useful in outlining types of international leadership represented by particular players. In realism international leaders (states) attempt at attaining their goals by maximizing their own power, security or by exerting influence. The tools and methods they use depend on their feeling of identity, therefore, they choose the path of aggression, negotiation or peaceful cooperation. Thanks to this and as a result of influence exerted by other international leaders and the structure itself, they occupy a particular position in the international environment. This position determines their attitude to each other and to the system in which they function (and vice versa). In this way international roles played by the international leaders are built. Such roles are not permanent. They require revision of observation of factors inside the state and in the system, as well as acceptance of other leaders (it is not enough for an actor to want to be a hegemonic leader to be acknowledged as such by others).